A tin-bismuth based low-temperature lead-free solder wire and a core wire thereof
Patent Information
- Application Number
- CN202611290884.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-25
AI Technical Summary
[0005]为此,本发明提供一种锡-铋基低温无铅焊锡线及其芯线,以解决现有技术中由于锡铋合金晶粒粗大、助焊剂芯线含卤族元素而导致的锡铋合金脆度大、易断裂、焊锡线无卤指标不达标和低温焊接可靠性差的问题
1、传统锡铋合金(Sn-Bi合金)晶粒粗大、晶界脆性相富集,受力易产生裂纹、发生断裂。本方案采用铟(In)、锑(Sb)微量复合改性体系实现双向增韧,金属In可固溶于Sn-Bi合金基体,改善合金的组织结构,弱化晶界脆性,提升合金基体延展性;金属Sb可强化合金晶界强度,有效抑制受力过程中微裂纹的产生与扩展,提升焊料的抗疲劳和抗弯折性能;二者协同作用,有效改善了Sn-Bi合金的固有脆性缺陷。此外,本发明对于锡铋合金的改性仅添加了铟和锑,未添加银、铜等金属,降低焊锡线成本的同时,简化了合金体系,避免了银、铜系合金的熔点高和易产生非均匀析出等缺陷。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of welding materials technology, specifically to a tin-bismuth-based low-temperature lead-free solder wire and its core wire. Background Technology
[0002] Solder wire is the most widely used and essential material in the electronic soldering field, extensively used in general electronic manufacturing scenarios such as household appliances, PCB soldering, and component lead soldering. Its soldering spatter, wetting properties, compatibility, and cost directly affect soldering yield, production efficiency, and product reliability. Low-temperature lead-free solder wire, as a new type of high-performance solder wire, typically requires low melting point, high toughness, good oxidation resistance, low residue, and environmental compliance. Traditional Sn-Bi low-temperature solder wire generally suffers from high brittleness, easy breakage, poor oxidation resistance, poor low-temperature wetting, and easy solder joint cracking, making it difficult to meet the reliable soldering requirements of precision electronics, flexible electronics, and heat-sensitive devices. To improve these problems, elements such as silver and copper are usually added to tin-bismuth alloys to prepare the alloy. This results in high cost of the prepared tin solder alloy, a tendency for non-uniform precipitation, poor process controllability, and affects the reliability of the solder joint.
[0003] The core function of flux is to remove the oxide film on the metal surface during the soldering process, reduce surface tension to promote wetting, and its performance determines the quality of the solder joint. Traditional fluxes generally suffer from poor wetting, severe solder spatter, and excessive residue under low-temperature soldering conditions. Furthermore, halogen-containing activators do not meet environmental protection requirements and their residues are hygroscopic, easily leading to short circuits on circuit boards.
[0004] Therefore, this invention proposes a tin-bismuth based low-temperature lead-free solder wire and its core wire to solve the above problems. Summary of the Invention
[0005] To address these issues, the present invention provides a tin-bismuth-based low-temperature lead-free solder wire and its core wire, thereby solving the problems in the prior art caused by the coarse grains of the tin-bismuth alloy and the presence of halogen elements in the flux core wire, resulting in high brittleness and easy breakage of the tin-bismuth alloy, substandard halogen-free solder wire performance, and poor low-temperature soldering reliability.
[0006] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a tin-bismuth-based low-temperature lead-free solder wire is provided, comprising a tin-bismuth alloy hollow wire blank and a core wire covered by the wire blank.
[0007] Further, the tin-bismuth alloy hollow wire blank comprises the following components by weight: 50-70 parts tin, 40-60 parts bismuth, 0.1-1 parts indium, and 0.1-1 parts antimony; the core wire is flux filling the interior of the wire blank; the flux accounts for 2-2.5% of the total mass of the solder wire.
[0008] Furthermore, the flux comprises the following components in parts by weight: 70-80 parts itaconic acid-4-vinylbenzoic acid copolymer, 10-20 parts acid-amino alcohol activator, 3-5 parts film-forming agent, 3-5 parts anti-spatter agent, and 1-5 parts defoamer.
[0009] Further, the acid-amino alcohol activator is obtained by mixing dodecanoic acid, D-phenylglycine, and 2-oxovaleric acid in a mass ratio of 3:5:2; the film-forming agent is styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether with a grafting rate of 30-35%; the anti-splatter agent is obtained by mixing fluorinated polysiloxane and fumed silica in a mass ratio of 1:1; and the defoamer is polyether-modified polydimethylsiloxane.
[0010] According to a second aspect of the present invention, a core wire of a tin-bismuth-based low-temperature lead-free solder wire is provided for preparing the aforementioned low-temperature lead-free solder wire.
[0011] According to a third aspect of the present invention, a method for preparing a tin-bismuth-based low-temperature lead-free solder wire is provided, which is used to prepare the above-mentioned solder wire, specifically including the following steps: S1. Smelting of tin-bismuth alloy: Tin, bismuth, antimony and indium are added to a vacuum melting furnace in a certain proportion, melted under vacuum conditions, stirred with nitrogen gas, and then degassed and cast to obtain a tin-bismuth alloy. S2. Preparation of flux: Itaconic acid-4-vinylbenzoic acid copolymer, dodecanedic acid, D-phenylglycine, 2-oxovalerate, styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, fluorinated polysiloxane, fumed silica, and polyether-modified polydimethylsiloxane were added to anhydrous ethanol at 55-60℃ in a certain proportion. The mass-to-volume ratio of the solid components of the flux to ethanol was 1 g: 2 mL. After mixing, the mixture was stirred at 200-400 rpm for 30-60 min. After stirring, the mixture was allowed to stand at room temperature for 2-4 h to stabilize the system properties, thus obtaining the flux. S3, Solder wire forming: The tin-bismuth alloy prepared by S1 was processed into tin-bismuth alloy hollow wire blanks with a diameter of 0.6-1 mm through multiple stages of wire drawing. The wire drawing and annealing temperature was 110-130℃. Flux is filled into the hollow tin-bismuth alloy wire blank using a core wire extrusion coating machine. After wire drawing, straightening, drying and cleaning, tin-bismuth based low-temperature lead-free solder wire is obtained.
[0012] Further, step S1 specifically includes the following steps: tin, bismuth, antimony and indium are put into a vacuum melting furnace in proportion, the vacuum is drawn to a vacuum degree of 0.03-0.05MPa, the temperature is raised to 240-260℃, and the temperature is kept constant for 20-40 minutes to melt all the metals; After melting, mechanically stir at 50-200 rpm for 10-20 min under a nitrogen atmosphere to ensure that antimony and indium are uniformly dissolved. After stirring, let it stand for 8 minutes to remove gas, then cast it into shape, cool and demold to obtain a tin-bismuth alloy.
[0013] Furthermore, the preparation method of the itaconic acid-4-vinylbenzoic acid copolymer in step S2 includes the following steps: Itaconic acid and an equimolar amount of 4-vinylbenzoic acid were dissolved in dimethyl sulfoxide. The mass-to-volume ratio of the mixture of itaconic acid and 4-vinylbenzoic acid to dimethyl sulfoxide was 0.1 g: 1 mL. 0.5% of the total mass of itaconic acid and 4-vinylbenzoic acid solids in AIBN was added, and the mixture was reacted in an oil bath at 60-80 °C for 8-12 h. After the reaction was completed, the mixture was cooled to room temperature, and ethanol was added to precipitate the product. The precipitate was filtered, dried, and the itaconic acid-4-vinylbenzoic acid copolymer was obtained.
[0014] Furthermore, the preparation of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether in step S2 specifically includes the following steps: The styrene-maleic anhydride copolymer was dissolved in 5 times its mass of N,N-dimethylformamide, and polyethylene glycol monomethyl ether was added. The reaction was carried out at 80-120℃ for 0.5-2 h. The molar ratio of styrene-maleic anhydride copolymer to polyethylene glycol monomethyl ether was (1-1.5):1. After the reaction was completed, N,N-dimethylformamide was separated by rotary evaporation, and the product was dried to obtain styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether.
[0015] According to a fourth aspect of the present invention, the application of the above-described tin-bismuth-based low-temperature lead-free solder wire in the fabrication of solder for micro-components or close-pitch devices is provided.
[0016] The present invention has the following advantages: 1. Traditional tin-bismuth alloys (Sn-Bi alloys) have coarse grains and are rich in brittle phases at grain boundaries, making them prone to cracking and fracture under stress. This solution employs a micro-composite modification system of indium (In) and antimony (Sb) to achieve bidirectional toughening. Metallic In can dissolve in the Sn-Bi alloy matrix, improving the alloy's microstructure, weakening grain boundary brittleness, and enhancing the alloy matrix's ductility. Metallic Sb can strengthen the alloy's grain boundary strength, effectively suppressing the generation and propagation of microcracks during stress, and improving the solder's fatigue and bending resistance. The synergistic effect of these two components effectively improves the inherent brittleness of Sn-Bi alloys. Furthermore, this invention modifies the tin-bismuth alloy by adding only indium and antimony, without adding metals such as silver or copper. This reduces the cost of solder wire while simplifying the alloy system and avoiding the high melting point and non-uniform precipitation defects of silver and copper alloys.
[0017] 2. This invention uses a composite of high-molecular polymers, a halogen-free organic acid-amino alcohol complex activation system, a film-forming agent, an anti-spatter agent, and a defoamer to prepare the flux. Zero-halogen raw materials are used to control halogen impurities. Furthermore, the organic acid-amino alcohol complex activation system can be rapidly activated in a low-temperature range of 160-190℃, efficiently removing the oxide layer from the solder and pad surfaces. The accompanying anti-spatter and defoamer components alleviate problems of bubbles, spatter, and carbonized residue during low-temperature soldering, improving the smoothness and reliability of precision electronic solder joints.
[0018] 3. This invention encapsulates halogen-free flux inside modified Sn-Bi alloy wire, achieving an integrated structure of solder matrix and flux. This avoids problems such as uneven flux coating and board surface contamination, ensuring uniform flux content and significantly improving the stability of low-temperature soldering and batch consistency of solder wire. Detailed Implementation
[0019] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] According to a first aspect of the present invention, a tin-bismuth-based low-temperature lead-free solder wire is provided, comprising a tin-bismuth alloy hollow wire blank and a core wire covered by the wire blank.
[0021] The tin-bismuth alloy hollow wire blank comprises the following components by weight: 50-70 parts tin, 40-60 parts bismuth, 0.1-1 parts indium, and 0.1-1 parts antimony; the core wire is flux filling the inside of the wire blank; the flux accounts for 2-2.5% of the total mass of the solder wire.
[0022] The flux comprises the following components by weight: 70-80 parts itaconic acid-4-vinylbenzoic acid copolymer, 10-20 parts acid-amino alcohol activator, 3-5 parts film-forming agent, 3-5 parts anti-spatter agent, and 1-5 parts defoamer.
[0023] The acid-amino alcohol activator is a mixture of dodecanedioic acid, D-phenylglycine, and 2-oxovaleric acid in a mass ratio of 3:5:2; the film-forming agent is a styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether at a grafting rate of 30-35%; the anti-splatter agent is a mixture of fluorinated polysiloxane and fumed silica in a mass ratio of 1:1; and the defoamer is a polyether-modified polydimethylsiloxane.
[0024] According to a second aspect of the present invention, a core wire of a tin-bismuth-based low-temperature lead-free solder wire is provided for preparing the aforementioned low-temperature lead-free solder wire.
[0025] According to a third aspect of the present invention, a method for preparing a tin-bismuth-based low-temperature lead-free solder wire is provided, which is used to prepare the above-mentioned solder wire, specifically including the following steps: S1. Smelting of tin-bismuth alloy: Tin, bismuth, antimony and indium are added to a vacuum melting furnace in a certain proportion, melted under vacuum conditions, stirred with nitrogen gas, and then degassed and cast to obtain a tin-bismuth alloy. S2. Preparation of flux: Itaconic acid-4-vinylbenzoic acid copolymer, dodecanedic acid, D-phenylglycine, 2-oxovalerate, styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, fluorinated polysiloxane, fumed silica, and polyether-modified polydimethylsiloxane were added to anhydrous ethanol at 55-60℃ in a certain proportion. The mass-to-volume ratio of the solid components of the flux to ethanol was 1 g: 2 mL. After mixing, the mixture was stirred at 200-400 rpm for 30-60 min. After stirring, the mixture was allowed to stand at room temperature for 2-4 h to stabilize the system properties, thus obtaining the flux. S3, Solder wire forming: The tin-bismuth alloy prepared by S1 was processed into tin-bismuth alloy hollow wire blanks with a diameter of 0.6-1 mm through multiple stages of wire drawing, and the wire drawing annealing temperature was 110-130℃. Flux is filled into the hollow tin-bismuth alloy wire blank using a core wire extrusion coating machine. After wire drawing, straightening, drying and cleaning, tin-bismuth based low-temperature lead-free solder wire is obtained.
[0026] Specifically, step S1 includes the following steps: tin, bismuth, antimony and indium are added to a vacuum melting furnace in proportion, the vacuum is drawn to a vacuum degree of 0.03-0.05MPa, the temperature is raised to 240-260℃, and the temperature is kept constant for 20-40 minutes to melt all the metals. After melting, mechanically stir at 50-200 rpm for 10-20 min under a nitrogen atmosphere to ensure that antimony and indium are uniformly dissolved. After stirring, let it stand for 8 minutes to remove gas, then cast it into shape, cool and demold to obtain a tin-bismuth alloy.
[0027] The preparation method of the itaconic acid-4-vinylbenzoic acid copolymer in step S2 includes the following steps: Itaconic acid and an equimolar amount of 4-vinylbenzoic acid were dissolved in dimethyl sulfoxide. The mass-to-volume ratio of the mixture of itaconic acid and 4-vinylbenzoic acid to dimethyl sulfoxide was 0.1 g: 1 mL. 0.5% of the total mass of itaconic acid and 4-vinylbenzoic acid solids in AIBN was added, and the mixture was reacted in an oil bath at 60-80 °C for 8-12 h. After the reaction was completed, the mixture was cooled to room temperature, and ethanol was added to precipitate the product. The precipitate was filtered, dried, and the itaconic acid-4-vinylbenzoic acid copolymer was obtained.
[0028] The preparation of styrene-maleic anhydride copolymer grafted polyethylene glycol monomethyl ether in step S2 specifically includes the following steps: The styrene-maleic anhydride copolymer was dissolved in 5 times its mass of N,N-dimethylformamide, and polyethylene glycol monomethyl ether was added. The reaction was carried out at 80-120℃ for 0.5-2 h. The molar ratio of styrene-maleic anhydride copolymer to polyethylene glycol monomethyl ether was (1-1.5):1. After the reaction was completed, N,N-dimethylformamide was separated by rotary evaporation, and the product was dried to obtain styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether.
[0029] To better illustrate the technical path of the present invention, the following embodiments and comparative examples are provided.
[0030] Example 1 S1. Smelting of tin-bismuth alloy: 2.85 kg of tin, 2.12 kg of bismuth, 0.02 kg of antimony and 0.01 kg of indium were put into a vacuum melting furnace, the vacuum was drawn to a vacuum degree of 0.05 MPa, the temperature was raised to 250°C, and the temperature was kept constant for 30 minutes to melt all the metals. After melting, the mixture is mechanically stirred at 100 rpm for 15 minutes under a nitrogen atmosphere to ensure that antimony and indium are uniformly dissolved. After stirring, let stand for 8 minutes to degas, then cast and cool to demold to obtain a tin-bismuth alloy. S2. Preparation of flux: Preparation of S201, itaconic acid-4-vinylbenzoic acid copolymer: 65.05 g of itaconic acid (purchased from Shanghai Baoyang Baoxin Biotechnology Co., Ltd., CAS: 97-65-4) and 74.08 g of 4-vinylbenzoic acid (purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd., CAS: 1075-49-6) were dissolved in 1391.3 mL of dimethyl sulfoxide, and 0.70 g of azobisisobutyronitrile (purchased from Shandong Yukang Chemical Co., Ltd., CAS: 78-67-1, AIBN) was added. The mixture was reacted in an oil bath at 70 °C for 10 h. After the reaction was completed, the mixture was cooled to room temperature, and ethanol was added to precipitate the product. The precipitate was filtered, dried, and the itaconic acid-4-vinylbenzoic acid copolymer was obtained. Preparation of S202, styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether: 15g of styrene-maleic anhydride copolymer (purchased from Wuhan Kemike Biomedical Technology Co., Ltd., CAS: 9011-13-6) was dissolved in 79mL of N,N-dimethylformamide, and 10g of polyethylene glycol monomethyl ether (purchased from Hubei Langbowan Biomedical Co., Ltd., CAS: 9004-74-4) was added. The reaction was carried out at 100℃ for 1h. After the reaction was completed, N,N-dimethylformamide was separated by rotary evaporation, and the product was dried to obtain styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether. After the preparation of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, its grafting efficiency was determined by acid-base titration, specifically including the following steps: Prepare 0.5M KOH-ethanol solution and 0.5M hydrochloric acid-isopropanol solution as titrants according to the method in GB / T 601—2016; wherein, the indicator for KOH-ethanol titrant is phenolphthalein and the primary standard is potassium hydrogen phthalate; the indicator for hydrochloric acid-isopropanol titrant is bromocresol green-methyl red and the primary standard is anhydrous sodium carbonate. Weigh 0.1g of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether into an Erlenmeyer flask, add 30mL of xylene, and heat under reflux for 30min until the graft copolymer is completely dissolved; after cooling, add 10mL of KOH-ethanol titrant, heat under reflux for 2h, cool to below the boiling point of ethanol, add 3 drops of phenolphthalein indicator, and titrate with hydrochloric acid-isopropanol titrant in a 60℃ water bath until the solution turns pink and remains so for 30s, which is the titration endpoint, and this is the back titration test; Then perform a blank test: add the same volume of KOH-ethanol titrant using a pipette, and titrate with hydrochloric acid-isopropanol titrant to the same titration endpoint; The grafting rate of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether is calculated using the following formula: ; Where c1 is the concentration of hydrochloric acid-isopropanol titrant (M); V0 is the volume of hydrochloric acid-isopropanol titrant consumed in the blank test (L); V1 is the volume of hydrochloric acid-isopropanol titrant consumed in the back titration (L); m is the mass of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether (g); and M0 is the molar mass of maleic anhydride (98.06 g / mol). The grafting rate of the styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether prepared by this invention was calculated to be 32.8% using this method. S203, 85.5g itaconic acid-4-vinylbenzoic acid copolymer, 4.39g dodecanedic acid (purchased from Greenlink (Jining) Chemical Technology Co., Ltd., CAS: 693-23-2), 7.31g D-phenylglycine (purchased from Hubei Benof Chemical Technology Co., Ltd., CAS: 56613-80-0), 2.93g 2-oxovaleric acid (purchased from Shanghai Maclean Biochemical Technology Co., Ltd., CAS: 1821-02-9), 5.1g styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, 2g fluorinated polysiloxane ( 2g of fumed silica (purchased from Wuhan Shuer Biotechnology Co., Ltd., CAS: 9004-74-4), 2g of fumed silica (purchased from Zhengzhou Songshan Boron Industry Technology Co., Ltd., surface energy 20-25mN / m), and 3.38g of polyether-modified polydimethylsiloxane (purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., model: HX-832, HLB value 3-5, viscosity 200-400cSt) were added to 225mL of anhydrous ethanol at 55℃; after mixing, the mixture was stirred at 300rpm for 30min, and after stirring, it was allowed to stand at room temperature for 3h to stabilize the system properties, thus obtaining the flux. S3, Solder wire forming: The tin-bismuth alloy prepared by S1 was processed into 0.8 mm diameter tin-bismuth alloy hollow wire blanks through multiple stages of wire drawing, and the wire drawing annealing temperature was 120℃. A core wire extrusion coating machine was used to fill 112.5g of flux into the interior of a 5kg tin-bismuth alloy hollow wire blank. After wire drawing, straightening, drying and cleaning, tin-bismuth-based low-temperature lead-free solder wire was obtained. During the wire drawing process, the ethanol component in the flux was removed.
[0031] Example 2 This embodiment is based on Embodiment 1, except that the mass of each component of the tin-bismuth alloy in step S1 is: 2835g tin, 2120g bismuth, 30g indium, and 15g antimony. The other specific parameters are the same as in Embodiment 1.
[0032] Example 3 This embodiment is based on Embodiment 1, except that the mass of each component of the tin-bismuth alloy in step S1 is: 2865g tin, 2120g bismuth, 10g indium, and 5g antimony. The other specific parameters are the same as in Embodiment 1.
[0033] Example 4 This embodiment is based on Embodiment 1, except that the amount of flux added in step S3 is 128.2g, while the other specific parameters are the same as in Embodiment 1.
[0034] Example 5 This embodiment is based on Embodiment 1, except that the amount of flux added in step S3 is 102.0g, while the other specific parameters are the same as in Embodiment 1.
[0035] Comparative Example 1 This comparative example is based on Example 1, except that the amount of flux added in step S3 is 144.0g, while the other specific parameters are the same as in Example 1.
[0036] Comparative Example 2 This comparative example is based on Example 1, except that the amount of flux added in step S3 is 91.6g, while the other specific parameters are the same as in Example 1.
[0037] Comparative Example 3 S1. Smelting of tin-bismuth alloy: 2.85 kg of tin, 2.12 kg of bismuth, 0.02 kg of antimony and 0.01 kg of indium were put into a vacuum melting furnace, the vacuum was drawn to a vacuum degree of 0.05 MPa, the temperature was raised to 250°C, and the temperature was kept constant for 30 minutes to melt all the metals. After melting, the mixture is mechanically stirred at 100 rpm for 15 minutes under a nitrogen atmosphere to ensure that antimony and indium are uniformly dissolved. After stirring, let stand for 8 minutes to degas, then cast and cool to demold to obtain a tin-bismuth alloy. S2, Solder wire forming: The tin-bismuth alloy prepared by S1 was processed into a 0.8 mm diameter tin-bismuth alloy hollow wire blank through multiple stages of wire drawing. The wire drawing annealing temperature was 120℃ to obtain tin-bismuth based low-temperature lead-free solder wire.
[0038] This comparative example is based on Example 1, except that no flux is added, while the other specific parameters are the same as in Example 1.
[0039] Comparative Example 4 This comparative example is based on Example 1, except that in step S2, itaconic acid-4-vinylbenzoic acid copolymer is replaced with low melting point hydrogenated rosin (purchased from Shandong Li'ang New Material Technology Co., Ltd., softening point 70-80℃, degree of hydrogenation ≥90%). The other specific parameters are the same as in Example 1.
[0040] Comparative Example 5 This comparative example is based on Example 1, except that in step S2, 14.63g of dodecanoic acid is used instead of 4.39g of dodecanoic acid, 7.31g of D-phenylglycine, and 2.93g of 2-oxovalerate. The other specific parameters are the same as in Example 1.
[0041] Comparative Example 6 This comparative example is based on Example 1, except that in step S2, 5.1g of itaconic acid-4-vinylbenzoic acid copolymer is used instead of styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, while the other specific parameters are the same as in Example 1.
[0042] Test Example 1 The present invention uses ICP-MS to detect the actual component content of the tin-bismuth alloy prepared in Example 1, and uses a halogen detector to detect the halogen residue of flux and solder wire products. The results are recorded in Table 1 and Table 2.
[0043] Table 1 Actual component content of tin-bismuth alloy
[0044] Note: "-" indicates that it is meaningless.
[0045] Table 2 Halogen Residues in Flux and Solder Wire Finished Products
[0046] As shown in Table 1, the solder wire prepared in Example 1 of this invention has few impurities, and the content of each component in the alloy deviates little from the theoretical value. This indicates that the alloy formulation and smelting process prepared by this invention have good precision and repeatability, and can stably achieve the designed composition. The results in Table 2 show that the flux and finished solder wire prepared by this invention have low halogen content, and the halogen-free index of the finished product is far below the industry limit, demonstrating good environmental advantages.
[0047] Test Example 2 To verify the effect of flux on the anti-spatter and residue of the solder wire prepared by the present invention, the solder wires prepared in Examples 1, 4, 5, and Comparative Examples 1-6 were subjected to low-temperature soldering at 170°C. The workpiece was a standard copper plate, and the spatter was observed. The results are recorded in Table 3.
[0048] Table 3. Solder wire spatter and residue.
[0049] As shown in Table 3, when the flux content is 2-2.5 wt% of the total solder wire mass, the solder wire exhibits good soldering wetting effect, excellent spatter control, and minimal residue, resulting in good batch-to-batch stability. Specifically, when the flux content is 2.2 wt% of the total solder wire mass (Example 1), it shows the best soldering wetting performance, spatter control, and residue control. However, when the flux content is increased to 2.5 wt% (Example 4), the spatter and residue of the solder wire increase. Further increasing to 2.8 wt% (Comparative Example 1), the solder wire exhibits significant over-wetting, with a marked increase in spatter and residue, and poor batch-to-batch quality stability. This is because during welding, the flux is heated instantaneously, causing the organic matter within it to decompose or vaporize violently. The resulting gas cannot escape in time, forming spatter. Furthermore, the organic matter is difficult to decompose completely within the extremely short welding time, forming carbonized residue and unreacted viscous substances. As the flux content increases, more gas is generated from the vaporization of organic matter, making it even more difficult for the organic matter to decompose completely, thus forming residue. When the flux content decreases to 2.0 wt% (Example 5) or even 1.8 wt% (Comparative Example 2), the content of the activating components in the flux decreases, making it unable to effectively wet the surface of the workpiece and remove the surface oxide film, hindering the wetting and spreading of the solder. At the same time, the removal of oxides is incomplete, leading to the formation of residue. Simultaneously, the amount of film-forming agent and anti-spatter agent decreases, making it difficult to form a complete protective film to stabilize the welding environment.
[0050] Comparative Example 4, which replaced itaconic acid-4-vinylbenzoic acid copolymer with hydrogenated rosin, exhibited insufficient wetting ability, localized cold solder joints, slight spatter, and a significantly increased amount of residue. This is because rosin has weak acidity and limited ability to remove oxides; its residues are prone to incomplete thermal decomposition, leaving residues, and are easily vaporized during soldering, generating spatter. Comparative Example 5, which did not add ammonia or keto acids to its activating component, using only dodecanoic acid as the activating component, exhibited insufficient wetting ability, localized cold solder joints, and a small amount of residue, but no significant spatter. This is because ammonia and organic acids can form complexes, which are more stable during soldering heating, less volatile, and can also improve the wettability of the solder to the soldered surface. Keto acids, due to their ideal decomposition temperature, near-zero residue, and low hygroscopicity, can effectively reduce flux residue during soldering. This result indicates that the flux in the solder wire prepared in this invention relies on the synergistic effect of organic acids and ammonia to activate its activity. Comparative Example 6, which did not contain the film-forming agent styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, exhibited the worst soldering performance among the three comparative examples. This is because the film-forming agent's role is to improve moisture resistance and form a uniform protective film to suppress spatter and reduce carbon residue. Comparative Example 3, which did not contain any flux, failed to wet the metal surface, resulting in numerous cold solder joints and a large amount of spatter and residue. The significant batch-to-batch quality variation in the solder wire also confirms the roles of each component in the flux.
[0051] Test Example 3 Based on the conclusions of Test Example 2, the present invention continues to use the solder wire prepared in Example 1 and Sn42Bi58 tin-bismuth alloy low melting point rosin core solder wire (purchased from Shenzhen Huajin Metal Technology Co., Ltd., melting point 138℃) for comparative testing. Wetting angle and wetting time were determined according to GB / T 11364-2008; spread rate was determined according to IPC-TM-6502.4.35; spatter rate was determined according to GB / T 25776-2010; residual carbide residue was determined according to GB / T 9741-2008; shear strength of the solder joint was determined according to GB / T 11363-2008; and solder joint failure rate after 1000 cycles at -40℃ to 125℃ was determined according to GB / T 2423.22-2012 to verify its low-temperature welding performance. The welding conditions were low-temperature welding at 170℃, and the workpiece was a standard copper plate. The results are recorded in Table 4.
[0052] Table 4. Comparison of low-temperature performance between Example 1 and Sn42Bi58 solder wire
[0053] As shown in Table 4, the solder wire prepared in Example 1 of this invention has good soldering performance. Under the soldering conditions of 170℃, the wetting angle is 18°, the wetting time is 0.8s, the spread rate is 87%, the solder spatter rate is ≤0.03%, there is no visible carbonized residue, the shear strength of the solder joint is 18.5MPa, and the solder joint failure rate is 0.5% after 1000 cycles of high and low temperature from -40℃ to 125℃. All of these are higher than the industry standard and significantly better than the Sn42Bi58 tin-bismuth alloy low melting point rosin core solder wire.
[0054] Test Example 4 This invention uses a universal testing machine to test the elongation at break, repeated bending life, and tensile strength of the wire, a Vickers hardness tester to test the Vickers hardness, and an impact testing machine to test the impact toughness at -20℃ to verify its mechanical properties. Due to time and cost considerations, only Examples 1, 2, and 3 were tested. Sn42Bi58 tin-bismuth alloy low-melting-point rosin core solder wire (purchased from Shenzhen Huajin Metal Technology Co., Ltd., melting point 138℃) and tin-copper lead-free rosin core solder wire (purchased from Shenzhen Huajin Metal Technology Co., Ltd.) were used as control groups for the experiment. The results are recorded in Table 5.
[0055] Table 5. Elongation at break, repeated bending life, tensile strength and impact toughness at -20℃ of solder wire
[0056] Table 5 shows that the modified Sn-Bi solder wires prepared in Examples 1-3 of this invention are significantly superior to traditional Sn42Bi58 tin-bismuth alloy solder wire and ordinary Sn-Cu lead-free solder wire in five mechanical properties: elongation at break, flexural life, tensile strength, Vickers hardness, and -20℃ low-temperature impact toughness. Example 1 showed the best performance, with an elongation at break of 52%, a flexural life of 28 cycles, and an impact toughness of 2.8 J / cm² at -20℃. 2 This indicates that the solder wire prepared in Example 1 can effectively improve the microstructure of the alloy, weaken grain boundary brittleness, and suppress the segregation of brittle phases at grain boundaries while increasing the hardness of the solder wire, thus simultaneously improving the elongation at break and impact toughness of the alloy. In contrast, Examples 2 and 3 showed a downward trend in mechanical properties due to deviations in the optimal ratio of In and Sb, indicating that there is an optimal synergistic range for the addition of In and Sb; too much or too little will not achieve the best toughening effect.
[0057] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A tin-bismuth-based low-temperature lead-free solder wire, characterized in that, Including tin-bismuth alloy hollow wire blanks and core wires covered by the wire blanks; The tin-bismuth alloy hollow wire blank comprises the following components by weight: 50-70 parts tin, 40-60 parts bismuth, 0.1-1 parts indium, and 0.1-1 parts antimony; the core wire is flux filling the interior of the wire blank; the flux accounts for 2-2.5% of the total mass of the lead-free solder wire. The flux comprises the following components by weight: 70-80 parts itaconic acid-4-vinylbenzoic acid copolymer, 10-20 parts acid-amino alcohol activator, 3-5 parts film-forming agent, 3-5 parts anti-spatter agent, and 1-5 parts defoamer; The acid-amino alcohol activator is a mixture of dodecanedioic acid, D-phenylglycine, and 2-oxovaleric acid in a mass ratio of 3:5:2; the film-forming agent is a styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether at a grafting rate of 30-35%; the anti-splatter agent is a mixture of fluorinated polysiloxane and fumed silica in a mass ratio of 1:1; and the defoamer is a polyether-modified polydimethylsiloxane. The preparation method of the itaconic acid-4-vinylbenzoic acid copolymer includes the following steps: Itaconic acid and an equimolar amount of 4-vinylbenzoic acid were dissolved in dimethyl sulfoxide. The mass-to-volume ratio of the mixture of itaconic acid and 4-vinylbenzoic acid to dimethyl sulfoxide was 0.1 g: 1 mL. Azobisisobutyronitrile (AIB) was added at 0.5% of the total mass of itaconic acid and 4-vinylbenzoic acid solids. The mixture was reacted in an oil bath at 60-80 °C for 8-12 h. After the reaction was completed, the mixture was cooled to room temperature, and ethanol was added to precipitate the product. The precipitate was filtered, dried, and the itaconic acid-4-vinylbenzoic acid copolymer was obtained. The preparation of the styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether specifically includes the following steps: The styrene-maleic anhydride copolymer was dissolved in 5 times its mass of N,N-dimethylformamide, and polyethylene glycol monomethyl ether was added. The reaction was carried out at 80-120℃ for 0.5-2 h. The molar ratio of styrene-maleic anhydride copolymer to polyethylene glycol monomethyl ether was (1-1.5):
1. After the reaction was completed, N,N-dimethylformamide was separated by rotary evaporation, and the product was dried to obtain styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether.
2. A core wire of a tin-bismuth-based low-temperature lead-free solder wire, prepared using the flux in the lead-free solder wire of claim 1.
3. A method for preparing tin-bismuth-based low-temperature lead-free solder wire, used to prepare the lead-free solder wire of claim 1, characterized in that, Specifically, the following steps are included: S1. Smelting of tin-bismuth alloy: Tin, bismuth, antimony and indium are added to a vacuum melting furnace in a certain proportion, melted under vacuum conditions, stirred with nitrogen gas, and then degassed and cast to obtain a tin-bismuth alloy. S2. Preparation of flux: Itaconic acid-4-vinylbenzoic acid copolymer, dodecanedic acid, D-phenylglycine, 2-oxovalerate, styrene-maleic anhydride copolymer grafted with polyethylene glycol monomethyl ether, fluorinated polysiloxane, fumed silica, and polyether-modified polydimethylsiloxane were added to anhydrous ethanol at 55-60℃ in a certain proportion. The mass-to-volume ratio of the solid components of the flux to ethanol was 1 g: 2 mL. After mixing, the mixture was stirred at 200-400 rpm for 30-60 min. After stirring, the mixture was allowed to stand at room temperature for 2-4 h to stabilize the system properties, thus obtaining the flux. S3, Lead-free solder wire forming: The tin-bismuth alloy prepared by S1 was processed into tin-bismuth alloy hollow wire blanks with a diameter of 0.6-1 mm through multiple stages of wire drawing. The wire drawing and annealing temperature was 110-130℃. Flux is filled into the hollow tin-bismuth alloy wire blank using a core wire extrusion coating machine. After wire drawing, straightening, drying and cleaning, tin-bismuth based low-temperature lead-free solder wire is obtained.
4. The preparation method according to claim 3, characterized in that, Step S1 specifically includes the following steps: tin, bismuth, antimony and indium are put into a vacuum melting furnace in proportion, the vacuum is drawn to a vacuum degree of 0.03-0.05MPa, the temperature is raised to 240-260℃, and the temperature is kept constant for 20-40 minutes to melt all the metals; After melting, mechanically stir at 50-200 rpm for 10-20 min under a nitrogen atmosphere to ensure that antimony and indium are uniformly dissolved. After stirring, let it stand for 8 minutes to remove gas, then cast it into shape, cool and demold to obtain a tin-bismuth alloy.
5. The application of a tin-bismuth-based low-temperature lead-free solder wire in the fabrication of solder for micro-components or close-pitch devices, characterized in that, The lead-free solder wire as described in claim 1 is used.
Citation Information
Patent Citations
Low-temperature lead-free soldering flux for tin-bismuth series
CN102489897A
Low-temperature lead-free formic acid solder paste and preparation method and application thereof
CN119973456A